KETERSEDIAAN SISTEM INFORMASI TERINTEGRASI TERHADAP KEPUASAN PENGGUNA - Firmanta Sebayang; Zeplin Jiwa Husada Tarigan (Jurnal Keuangan dan Perbankan, 2009)
There were two major questions being discussed in this research, i.e. firstly, how todetermine the support of the top management and environment uncertainty and their influenceto the preparation of technology information system; secondly, how to determine the influenceof preparation technology information system to information sharing and information qualitywhich used information technology to end user satisfaction Based on previous research. It wasfound that preparation of technology information system was influenced by top managementbecause information system was determined by top management, and environment uncertaintywould influence the provide of data management. Based on a survey which was conducted bymeans of interviews and questionnaires to 53 end user information technology systempractitioners in this research, it was found that in the preparation for an integrated informationtechnology, support top management as an organization and environment uncertainty as outof organization was a requirement to form preparation of information technology system. Aninformation technology system was able to be an information sharing and information quality,but it could not directly bring the end user satisfaction. The result of an information sharingand information quality directly impacted to end user satisfaction.